ROLE OF PROFESSIONAL EDUCATION IN DEVELOPING ENTREPRENEURIAL SKILL AMONG FEMALE STUDENTS AN EMPIRICAL RESEARCH - Chahar, Dr. Bhawna (International Journal of Psychosocial Rehabilitation, 2020)
Women entrepreneurship has witnessed phenomenal growth and gaining significant importance in higher educational policy of Indian government in the wake of liberalization, and globalization. Indian Government has taken several measures to promote entrepreneurship among women and bridge the gender gap created socio economic inequality. Both central and state government in association with several government and nongovernment organization has taken initiative to develop entrepreneurial skill through professional education and make them empowered. The present paper focus on role of professional education in promoting entrepreneurial skill among female students. The cross-sectional study method was used by researcher in this study. The sample consists 209 female students doing professional courses in the various engineering and management institutes of Rajasthan state. Factors of professional education and outcome of professional education on entrepreneurial skill were identified from secondary literatures. Validity and reliability of the construct and their interrelatedness were measured and tested using SPSS software. Finding indicates positive association between professional education and entrepreneurial skill. It is found that family background moderates the relationship between professional education and entrepreneurial skill. It has been seen that professional education helps the candidates to improve their skills and other entrepreneurial outlook like being the independent boss etc. Some of the conclusion and managerial implication based on study were also drawn and presented in the study.